The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1128/jcm.42.1.212-219.2004
|View full text |Cite
|
Sign up to set email alerts
|

IS 6110 Mediates Increased Transcription of the phoP Virulence Gene in a Multidrug-Resistant Clinical Isolate Responsible for Tuberculosis Outbreaks

Abstract: Drug resistance in Mycobacterium tuberculosis complex strains is solely due to chromosomal mutations that could affect bacterial virulence. Molecular epidemiology studies have shown that resistant strains are less likely to be clustered than susceptible strains. However, a few multidrug-resistant (MDR) M. tuberculosis complex strains have been described as causing outbreaks, suggesting that they have restored virulence or increased transmission. One of the biggest MDR tuberculosis outbreaks documented to date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 47 publications
(51 reference statements)
3
104
0
1
Order By: Relevance
“…66 H37Ra is also defective in PDIMs, but this phenotype is not caused by the phoP mutation. 63 Collectively, these studies have demonstrated that the PhoP-PhoR system, particularly PhoP, plays an essential role in M. tb virulence. 62,65,66,69 Considering its prominent role in virulence, it may not be surprising that BCG strains exhibit a number of genetic polymorphisms in the phoP-phoR locus.…”
Section: Correlation With Residual Virulence and Reactogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…66 H37Ra is also defective in PDIMs, but this phenotype is not caused by the phoP mutation. 63 Collectively, these studies have demonstrated that the PhoP-PhoR system, particularly PhoP, plays an essential role in M. tb virulence. 62,65,66,69 Considering its prominent role in virulence, it may not be surprising that BCG strains exhibit a number of genetic polymorphisms in the phoP-phoR locus.…”
Section: Correlation With Residual Virulence and Reactogenicitymentioning
confidence: 99%
“…69 In M. tb, defective biosynthesis of trehalose-containing lipids does not explain the attenuated phenotype of the phoP mutant, but impaired ESX-1 secretion might. 63 In the avirulent lab strain, H37Ra, attenuation is partially explained by a single point mutation (S219L) in the DNA binding region of PhoP. 66 H37Ra is also defective in PDIMs, but this phenotype is not caused by the phoP mutation.…”
Section: Correlation With Residual Virulence and Reactogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Transposable elements can also act by modifying the expression of neighbouring genes at the integration site, or by promoting huge genomic rearrangements when they are substrates for homologous recombination (Casacuberta & González, 2013;Mahillon & Chandler, 1998;Maruyama et al, 2009). Some well-described bacterial examples are the activation of the cryptic bgl and cel operons required for utilization of b-glucoside sugars in Escherichia coli by disruption of silencer elements around the promoter region by IS1, IS2 or IS5 transposition; IS1 insertion into the mgl locus improving the glucose transport and fitness of E. coli; ISS12 integration into the srpS gene increasing the resistance of Pseudomonas putida to toluene by derepressing the genes encoding an inducible solvent resistance pump; or IS6110 controlling transcription of Mycobacterium tuberculosis genes (including the phoP virulence gene) downstream of its integration site through an outward-directed promoter located at its 39 end (Hall, 1998;Notley-McRobb & Ferenci, 1999;Parker & Hall, 1990;Safi et al, 2004;Soto et al, 2004;Wery et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Another example of molecular mechanisms possibly involved in virulence of drug resistant strains is the regulation of genes mediated by IS6110. This insertion sequence appears to be associated with the upregulation of genes implicated in virulence of Beijing strains and other clinical strains that have caused MDR-TB outbreaks (101,102). Further studies with this family of strains will reveal the molecular mechanisms involved in virulence, if in fact these strains are more virulent than others, and their impact on the worldwide tuberculosis epidemic.…”
Section: The Beijing Genotype and Virulence Of M Tuberculosismentioning
confidence: 99%